IMPLEMENTASI KEAMANAN BERKAS MENGGUNAKAN TEKNIK STEGANOGRAFI DAN ALGORITMA KRIPTOGRAFI MENGGUNAKAN METODE LEAST SIGNIFICANT BIT (LSB) DAN ALGORITMA RIVEST CODE 4 (RC4) - Novianto, Dian (JUTIM (Jurnal Teknik Informatika Musirawas), 2018)
AbstractData security is an important factor in an electronic transaction, because the data sent must only be known to the person who is entitled to receive the information. There are several security aspects of the data that must be maintained, such as: authentication, integrity, non repudiation, authority, confidentialty, privacy and access control. Therefore we are need for a system that is capable of carrying out some of these aspects. One technique that can be used in maintaining data security is steganography with the LSB (Least Significant Bit) method. In addition, to strengthen the confidentiality of the hidden information in steganography needed Additional techniques in the form of cryptography namely RC4 (Rivest Code 4). In this research,, the researcher  used a software development model is a prototype. And for the tools used in developing this application is an Unified Modeling Language. The results of the research conducted by researchers are the application of steganography using the LSB (Least Significant Bit) method combined with RC4 cryptography (Rivest Code 4) proven to be able to hide and secure important information from people who do not have access rights to that information. Keywords: Steganography, Criptography, Data Security